SAP business analytics : a best practices guide for implementing business analytics using SAP - DuttaRoy, Sudipa (Apress, 2016)
Focus on SAP business analytics business gains, key features, and implementation. The book includes example implementations of SAP business analytics, the challenges faced, and the solutions implemented. SAP Business Analytics explains both the strategy and technical implementation for gathering and analyzing all the information pertaining to an organization. Key features of the book are: A 360-degree view of an organization's data and the methods to gather and analyze that data The strategies that need to be in place to gather relevant data from disparate systems Details about the SAP business analytics suite of products The technical implementations used to gather data from disparate systems such as ERP and CRM Real business cases as examples Analytics is the driving force in today's business, be it healthcare, marketing, telecommunications, or retail and hence the most vital part of any organization's strategy. What You'll Learn Gain an understanding of business analytics in general Absorb the technical details of the SAP business analytics suite of products Discover the challenges faced during an enterprise-level analytics project implementation Learn the key points to be kept in mind during the technical implementation of an SAP business analytics project Who This Book Is For Analytics strategists, BI managers, BI architects, business analysts, and BI developers.